2007
DOI: 10.1016/j.ntt.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Decreased sensitivity in adolescent vs. adult rats to the locomotor activating effects of toluene

Abstract: Volatile organic solvent (inhalant) abuse continues to be a major health concern throughout the world. Of particular concern is the abuse of inhalants by adolescents because of its toxicity and link to illicit drug use. Toluene, which is found in many products such as glues and household cleaners, is among the most commonly abused organic solvents. While studies have assessed outcomes of exposure to inhalants in adult male animals, there is little research on the neurobehavioral effects of inhalants in female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 62 publications
5
26
0
Order By: Relevance
“…In this study, we demonstrated that the toluene effect also depended on animal age. The age-dependence of the toxic effects was also demonstrated in our previous studies [6,7] and in some other reports [2]. We previously showed more rapid motor learning in young rats after chronic toluene inhalation in comparison with adult animals [6].…”
Section: Figsupporting
confidence: 80%
See 2 more Smart Citations
“…In this study, we demonstrated that the toluene effect also depended on animal age. The age-dependence of the toxic effects was also demonstrated in our previous studies [6,7] and in some other reports [2]. We previously showed more rapid motor learning in young rats after chronic toluene inhalation in comparison with adult animals [6].…”
Section: Figsupporting
confidence: 80%
“…The effect of chronic toluene inhalation largely depends on toxicant dose and animal sex [2,4]. In this study, we demonstrated that the toluene effect also depended on animal age.…”
Section: Figmentioning
confidence: 58%
See 1 more Smart Citation
“…Taken together, these results imply that abuse of organic solvents during pregnancy in humans may result in greater risks to fetuses and neonates than continuous exposures at lower concentrations. It is important to note that developmental shifts in sensitivity to the negative consequences of binge organic solvent exposures extend into early postnatal life, in both neonatal models of third-trimester exposures and -although not within the scope of this reviewinto adolescence, a period of enhanced risk for toluene abuse (cf., [Bowen et al 2007a]). Prenatal exposure to toluene produces significant doseresponse shifts in psychopharmacological responses that may be indicative of neural mechanisms for the neurobehavioral disturbance associated with fetal solvent syndrome.…”
Section: Neurobehavioral Teratologymentioning
confidence: 99%
“…Only a handful of studies have examined gross dysmorphology following patterns of prenatal toluene exposure that mimic inhalant abuse (i.e., repeated, high dose short exposures) [8,10,12,26,59]. In previous work examining prenatal binge toluene exposure, repeated 15 min (8,000 or 12,000 ppm) exposure twice a day (30 min total per day) from Gestation Day 8 (GD8) through GD20 produced significant increases in total minor and gross malformations, including reduced body weight, soft tissue anomalies (e.g., missing eyes), and skeletal abnormalities (shortened and/or missing digits and missing limbs, reduced skeletal ossification), "runting" and fetal or postnatal death [8,51].…”
Section: Introductionmentioning
confidence: 99%